2023
DOI: 10.1001/jamaoncol.2022.5153
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Risk Among Older Cancer Survivors Compared With Older Adults Without a History of Cancer

Abstract: ImportanceThe number of cancer survivors living in the US is projected to be 26.1 million by 2040. Cancer survivors may be at increased risk of bone fractures, but research is limited in several important ways.ObjectiveTo investigate the associations of cancer diagnoses, including time since diagnosis and stage at diagnosis, with risks of pelvic, radial, and vertebral fractures (separately and combined) among older cancer survivors and compared with fracture risk among older adults without a history of cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Likewise, common chemotherapeutic agents have been found in correlation with enhanced bone resorption in premenopausal BC patients [137], which is consistent with findings from a longitudinal cohort study (N = 92,431) [133].…”
Section: Conventional Breast Cancer Treatment-induced Secondary Osteo...supporting
confidence: 86%
See 1 more Smart Citation
“…Likewise, common chemotherapeutic agents have been found in correlation with enhanced bone resorption in premenopausal BC patients [137], which is consistent with findings from a longitudinal cohort study (N = 92,431) [133].…”
Section: Conventional Breast Cancer Treatment-induced Secondary Osteo...supporting
confidence: 86%
“…These data demonstrate the tremendous positive impact of early diagnosis and effective treatment options. Nevertheless, it is crucial to evaluate potential side effects associated with BC therapies such as surgical oophorectomy, chemotherapy-induced ovarian failure, and anti-estrogenic hormone therapies, including aromatase inhibitors, on the maintenance of a high quality of life for cancer survivors [ 132 , 133 ].…”
Section: Epigenetic Changes As Key Driving Factor Of Breast Cancer An...mentioning
confidence: 99%
“…Nonetheless, in vivo and in vitro studies have shown that cytotoxic chemotherapeutic agents such as epirubicin ( Huang et al, 2018 ), methotrexate ( Georgiou et al, 2012 ; Shandala et al, 2012 ), doxorubicin (DOX) ( Fan et al, 2017 ; Yao et al, 2020 ; Rana et al, 2013 ), cyclophosphamide ( Fan et al, 2017 ), and melphalan ( Chai et al, 2017 ) can induce bone loss through multiple mechanisms that do not involve hormone deprivation. While it is not yet clear to what extent these cytotoxic agents contribute to CTIBL in cancer survivors, a recent cohort study revealed that older cancer survivors who received chemotherapy had a higher risk of fragility fractures than older adults without cancer ( Rees-Punia et al, 2023 ). The results of this study indicate that chemotherapy has a significant impact on long-term bone health in cancer survivors and underlines the importance of understanding the effects and mechanisms of chemotherapeutic agents on CTIBL.…”
Section: Introductionmentioning
confidence: 99%